Larvul Ngabal as the Basis for Interreligious Harmony: The Central Role of the Raja in the Kei Islands - Nurdin, Roswati (LPPM IAIN Parepare, 2024)
The Kei Islands community is known as a community that lives by upholding the customs of Larvul Ngabal led by a king or in the term of the Kei island community called Rat. He serves as an informal leader who is equal to the head of government within the scope of indigenous peoples. This research answers the problem of how the role of customary leadership in maintaining religious harmony on the Key islands. The method used is descriptive qualitative with structured interview data collection techniques from kings, traditional leaders, community leaders, youth and migrant communities. The results showed that the role of the king or Rat and its legal structure as a conflict mediator has a role in maintaining the religious harmony of the Kei community. The position of the king as a representative of God or God and is the second head after the head of God, is a link between custom and religion and is respected by the community. As the head of customary government, the king has legal legitimacy over customary institutions including the head of the Ohoi/Ohoi Rat government and all natural resource wealth. The role of the king and his legal structure as a decision-maker at customary sessions or decisions made by the king himself are obeyed and adhered to by his community within the framework of obedience to the customary law of Larvul Ngabal which is considered sacred and sacred.